Overexpression of cannabinoid receptor 1 in esophageal squamous cell carcinoma is correlated with metastasis to lymph nodes and distant organs, and poor prognosis. Issue 2 (15th December 2016) - Hijiya, Naoki; Shibata, Tomotaka; Daa, Tsutomu; Hamanaka, Ryoji; Uchida, Tomohisa; Matsuura, Keiko; Tsukamoto, Yoshiyuki; Nakada, Chisato; Iha, Hidekatsu; Inomata, Masafumi; Moriyama, Masatsugu
Abstract : In patients with esophageal squamous cell carcinoma (ESCC), the status of metastasis to lymph nodes is strongly associated with prognosis. Consequently, development of a biomarker to detect the presence of metastasis would be clinically valuable. In this study, we found that overexpression of cannabinoid receptor 1 (CB1R) was applicable as a marker for prediction of metastasis in ESCC. CB1R overexpression was detected immunohistochemically in 54 of 88 cases (61.4%). The intensity of CB1R expression was uniform in both intraepithelial and invasive regions in each case, and was significantly correlated with the status of metastasis to lymph nodes ( P = 0.046) and distant organs ( P = 0.047). Furthermore, multivariate analysis revealed that CB1R overexpression was independently associated with poor prognosis ( P = 0.019). Biological analysis of CB1R overexpression using ESCC cell lines revealed that CB1R activation appeared to promote cell proliferation and invasion. On the basis of these findings, we propose that evaluation of CB1R expression status in biopsy specimens of ESCC using immunohistochemistry might be clinically useful for prediction of metastasis to lymph nodes and distant organs.